Do moral philosophies influence auditors’ ethical judgments? / Maheran Zakaria, Hasnah Haron and Ishak Ismail - Zakaria, Maheran; Haron, Hasnah; Ismail, Ishak (Universiti Teknologi MARA Cawangan Selangor, 2010)
The increasing number of financial scandals resulting from auditors’ unethical judgment has led to public distrust on the morality of auditors. Hence, the message is clear; to be relevant, auditors must be ethical in their behavior and judgments. As such, it is important to understand and investigate factors that influence auditors’ ethical judgments. This paper attempts to examine the influence of two moral philosophies namely deontology and teleology evaluations on auditors’ ethical judgments. A total of 940 questionnaires were sent to audit firms in Malaysia. About 250 auditors responded with 224 questionnaires were usable. By using Structural Equation Modeling of AMOS 16.0, the study found that there were significant relationships between these two philosophies namely deontology and teleology evaluations on auditors’ ethical judgments. Findings of this study will be useful for Malaysian Institute of Accountants (MIA), the government, audit firms and institutions of higher learning in their effort to improve auditors’ ethical judgments which can uphold the credibility and viability of the auditing profession.